Ameliorating children's reading-comprehension difficulties: a randomized controlled trial. - Clarke, P; Snowling, M; Truelove, E; Hulme, C (2010)
Children with specific reading-comprehension difficulties can read accurately, but they have poor comprehension. In a randomized controlled trial, we examined the efficacy of three interventions designed to improve such children's reading comprehension: text-comprehension (TC) training, oral-language (OL) training, and TC and OL training combined (COM). Children were assessed preintervention, midintervention, postintervention, and at an 11-month follow-up. All intervention groups made significant improvements in reading comprehension relative to an untreated control group. Although these gains were maintained at follow-up in the TC and COM groups, the OL group made greater gains than the other groups did between the end of the intervention and follow-up. The OL and COM groups also demonstrated significant improvements in expressive vocabulary compared with the control group, and this was a mediator of the improved reading comprehension of the OL and COM groups. We conclude that specific reading-comprehension difficulties reflect (at least partly) underlying oral-language weaknesses that can be effectively ameliorated by suitable teaching.